Comparative study of vanilloids in cell cultures - Atzeni, A.; Rosa, A.; Appendino, et al., G. (Progress in Nutrition, 2012)
Free radical reaction of lipid peroxidation in cell membranes is responsible for the degradation of unsaturated fatty acids, and produces a variety of products that can be used as biomarkers of the extent of the oxidation. The oxidative modification of lipids in the human body is inhibited by endogenous antioxidative defence systems as well as by dietary antioxidants. Capsiate, the archetypal capsinoid, has been obtained from the fruits of a nonpungent cultivar of Capsicum annuum L. (CH-19 Sweet). This vanilloid compound, a simple phenol, is non-offensive and devoid of pungency, and has been shown several and interesting biological activities. In this study we have compared the activity of synthetic capsiate, a simplified analog of capsiate, and vanillyl alcohol, its hydrophilic hydrolytic metabolite, on the oxidative stress induced by tert-butyl hydroperoxide (TBH) in a line of fibroblasts derived from monkey kidney (Vero cells). In response to the TBH mediated oxidative stress, a reduction of the levels of total unsaturated fatty acids was observed, and a rise in the concentrations of conjugated dienes fatty acids hydroperoxides in Vero cells. Pre-treatment with both synthetic capsiate and vanillyl alcohol preserved Vero cell from oxidative damage and showed remarkable protective effect on the reduction of the levels of total unsaturated fatty acids, inhibiting the increase of MDA and hydroperoxides. Both compounds were effective against peroxidation of cell membrane lipids induced by TBH. Key words: Capsicum annuum L., antioxidants, capsiate, vanillyl alcohol, lipid peroxidation, Vero cells Studio comparativo dei vanilloidi in colture cellulari La reazione radicalica di perossidazione lipidica nelle membrane cellulari è responsabile della degradazione degli acidi grassi insaturi e porta alla formazione di una serie di prodotti di ossidazione che possono essere utilizzati come indicatori dell’estensione del danno ossidativo. La modificazione ossidativa dei lipidi, che avviene all’interno dell’organismo umano, può essere contrastata dai sistemi di difesa antiossidanti endogeni, e dagli antiossidanti assunti tramite la dieta. Il capsiato, capsinoide modello, è stato isolato dai frutti di una cultivar non piccante di Capsicum annuum L. chiamata CH-19 Sweet. Questo composto vanilloide, fenolo semplice privo di potere piccante e irritante, ha mostrato interessanti attività biologiche. In questo lavoro è stata comparata l’attività antiossidante del capsiato sintetico, un analogo chimico semplificato del capsiato naturale, con quella dell’alcol vanillico, suo metabolita idrolitico idrofilico, nei confronti del danno ossidativo indotto dal terz-butilidroperossido (TBH) in cellule Vero, una linea immortalizzata di fibroblasti di rene di scimmia. Nelle cellule Vero, in seguito al trattamento con il TBH, è stata osservata una riduzione dei livelli degli acidi grassi insaturi e un aumento della concentrazione degli idroperossidi degli acidi grassi a dieni coniugati. Il pre-trattamento con il capsiato sintetico e l’alcol vanillico ha preservato le cellule Vero dal danno ossidativo indotto dal TBH e ha mostrato un significativo effetto protettivo sulla riduzione degli acidi grassi insaturi, inibendo l’aumento dei livelli di MDA e di idroperossidi. Entrambi i composti sono risultati efficaci nei confronti della perossidazione dei lipidi delle membrane cellulari indotta dal TBH.